Using social theory thinking through research - Pryke, Michael, 1955-; Rose, Gillian, 1962-; Whatmore, Sarah. (SAGE, 2003)
As the authors demonstrate, research is not simply 'done', it's got to be thought about and thought through. 'Using Social Theory's' accessible style makes it suitable for anyone wishing to engage with ideas in research in the social sciences and humanities.